Multi-point varactorloaded tunable ring-based bandpass filters / Muhamad Aidi Abdul Latip - Abdul Latip, Muhamad Aidi (2015)
Current demand of the microwave application systems requires an optimum exploitation of the frequency spectrum, leading to rigorous specifications imposed on microwave filters, in terms of cost, compactness and selectivity. Along such direction, tunable filters are becoming ideal solution to replace bulky and complicated filter banks, which are required to cater the multiple channels due increasing number of applications in the system. A novel concept of tunable dual-mode ring resonator filter involving quarter-wavelength coupled-lines has been introduced, based on the identification of the filter control parameters. However, no specific method or practical implementation of the concept has been proposed to achieve the concept. In addition, no precise technique or technology has been suggested to allow the addition of the tuning elements into the filter to allow the tuning. Therefore, the main objective of this thesis work is to realize the proposed tunable ring-based filter using one of the reliable tunable technologies which is varactor diode that can satisfy fast tuning speed, low cost, ease of fabrication and wide selection. In order to achieve this, a tuning circuit is proposed, designed and implemented. Then, the varactor-tuned circuit is applied into the quarter-wavelength side-coupled ring-resonator filter. The proven tuning circuit is also used to realize other types of tunable filters, based on two developed ring-based topologies. Furthermore, the complete circuits of the tunable bandpass filter are realized using microstrips on epoxy glass substrate and the measurement results are found to be in good agreement with the ones from simulation.